Blood cell count is not a significant predictor of survival in bladder cancer after radical cystectomy - Andy, Andy; Prapiska, Fauriski Febrian; Siregar, Ginanda Putra; Warli, Syah Mirsya; Sihombing, Bungaran (Faculty of Medicine, Universitas Trisakti, 2021)
BackgroundRadical cystectomy (RC) is the gold standard treatment for muscle-invasive bladder carcinoma. A predictive factor is needed for the aggressive approach as it could lead to overtreatment. Elevated blood cell count (BCC) markers are reported to have a significant association with poor outcomes in several types of malignancy. Neutrophil-to-lymphocyte-ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are well-known inexpensive and effective representative markers of inflammatory conditions. This study aimed to determine the BCC as a predictive factor of overall survival (OS) in patients with bladder carcinoma (BC) after RC. MethodsA retrospective cohort study was conducted involving 26 patients who had undergone RC. The demographic characteristics and BCC markers such as hemoglobin (Hb). NLR, PLR and lymphocyte/monocyte ratio (LMR) were collected. The patients were categorized based on the BCC marker value (³ median and < median). Kaplan–Meier survival analysis was done to determine overall survival (OS) on BCC markers. The association between patient demographics and one-year survival was also determined using Mantel-Cox (Log-rank) method. ResultsAmong the 26 patients, the mean age was 55.6 ± 12.9 years. On univariate analysis, none of the demographic characteristics was found to be a significant predictor of one-year and overall survival (p>0.05). Hemoglobin, NLR, PLR and LMR were not significant predictors of one-year survival and OS (p>0.05). ConclusionsThe BCC was not a significant predictive factor of survival in patients with bladder cancer after radical cystectomy.